Extending the sequences of HLA class I alleles without full‐length genomic coverage using single molecule real‐time DNA sequencing. (21st January 2020) - Hassall, Kylara B.; Latham, Katy; Robinson, James; Gymer, Arthur; Goodall, Rebecca; Merlo, Dario; Marsh, Steven G. E.; Mayor, Neema P.
Abstract : The assignment of an HLA allele name to a sequence requires a comparison between the generated target sequence and a reference sequence on the IPD‐IMGT/HLA database. Absence of a full‐length reference sequence can result in the inability of HLA typing software to accurately compare and assign the sequence. We sequenced the most frequently seen HLA class I alleles on the Anthony Nolan register present in the database with only a partial genomic sequence, with the aim of increasing the number of complete reference sequences. We successfully extended 95 full‐length HLA class I sequences and identified 13 novel variants. Increasing the number of full‐length HLA class I reference sequences in the database has aided accuracy of HLA analysis tools for all histocompatibility and immunogenetics laboratories.